2020
DOI: 10.3390/ijms21072286
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Tumor-Immune Escape: Biological Functions and Clinical Perspectives

Abstract: The modulation of the immune system is one of the hallmarks of cancer. It is now widely described that cancer cells are able to evade the immune response and thus establish immune tolerance. The exploration of the mechanisms underlying this ability of cancer cells has always attracted the scientific community and is the basis for the development of new promising cancer therapies. Recent evidence has highlighted how extracellular vesicles (EVs) represent a mechanism by which cancer cells promote immune escape b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 152 publications
(184 reference statements)
0
46
0
Order By: Relevance
“…Since Tregs suppress the activity of effector T-cells, hypoxia tends to create an immunosuppressive TME. Moreover, HIF1-α works as a direct inducer of PD-L1 (Programmed Death-Ligand 1) expression in cancer cells, macrophages, dendritic cells, and MDSCs, resulting in further effector T-cell inhibition and enhancing tumor immune escape [ 71 , 72 ]. In contrast to previous findings, it has been reported that HIF1-α stimulates immune activation by positively modulating the function of cytotoxic T-cells and contributing to NK cell activation [ 73 , 74 ].…”
Section: Dual Role Of Hypoxia In Inflammation and Immune System Rementioning
confidence: 99%
“…Since Tregs suppress the activity of effector T-cells, hypoxia tends to create an immunosuppressive TME. Moreover, HIF1-α works as a direct inducer of PD-L1 (Programmed Death-Ligand 1) expression in cancer cells, macrophages, dendritic cells, and MDSCs, resulting in further effector T-cell inhibition and enhancing tumor immune escape [ 71 , 72 ]. In contrast to previous findings, it has been reported that HIF1-α stimulates immune activation by positively modulating the function of cytotoxic T-cells and contributing to NK cell activation [ 73 , 74 ].…”
Section: Dual Role Of Hypoxia In Inflammation and Immune System Rementioning
confidence: 99%
“…sEV have gained interest due to their essential role in “normal” intercellular signaling and communication, which impact the physiological balance and homeostasis as well as disease progression. [ 1 , 6 , 32 , 33 , 34 , 35 , 36 ]. Importantly, sEV can modulate the phenotype/functions of recipient cells, even those located in distant organs [ 2 , 3 , 35 , 36 , 37 , 38 ].…”
Section: General Characteristics Of Sevmentioning
confidence: 99%
“…Immunosuppressive activity of MTEX depends on their ligands that engage the T cell receptor (TCR) and IL-2 receptor (IL-2R). Recent studies showed that MTEX inhibited signaling and proliferation of activated primary CD8 + T cells, inducing their apoptosis [ 25 , 32 , 90 ]. Furthermore, MTEX significantly promoted conversion of CD4(+) T cells to CD4(+)CD25(+)FOXP3(+) T regulatory cells (Treg) enhancing their suppressor functions [ 25 ].…”
Section: Biological Activity Of Mtexmentioning
confidence: 99%
“…The inexplicable nature of exosomes has raised concern about their role in the invasion and metastasis of cancer cells, encompassing epithelial-to-mesenchymal transition (EMT), angiogenesis, and immune regulation [ 12 ]. Thus, instead of reviewing the isolated impact of exosomes, e.g., evasion of immune surveillance [ 13 ] for cancer progression, we have tried to encompass exosome-mediated propagation of oncogenic signaling, epigenetic regulation, modulation of tumor microenvironment (TME) and immune escape, EMT, angiogenesis, metastasis and drug resistance. Considering the clinical applications, the exosomes serve as potent diagnostic and prognostic biomarkers because of their bioavailability, low toxicity and differentiated surface markers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%